Sentiment analysis of Indonesia’s new digital Tax Administration System (Coretax) - Shelvi, Shelvi; Rachdian, Adinda Oktaviani; Pawitan, Gandhi; Sari, Diana (Accounting Department, Faculty of Business and Economics, Universitas Islam Indonesia, 2025)
This study explores public sentiment toward Indonesia’s new digital tax administration system, known as Coretax, by analyzing conversation among tax-savvy users in a WhatsApp Group. Public sentiment was analyzed by examining more than 53,000 messages using a lexicon-based approach to classify them into positive, negative or neutral categories. The findings reveal that negative sentiment dominates (39%), indicating frequent technical issues, procedural confusion, and access problems during Coretax’s early implementation phase in 2025. However, neutral (31.5%) and positive (29.5%) messages show that users also shared information and expressed appreciation, especially during successful interactions. Spikes in communication occurred during major events such as webinars and statutory tax filing deadlines. This study provides a novelty using real-time peer-to-peer digital conversations to capture how knowledgeable users experience tax digitalization in its earliest months. The findings suggest that user-oriented design, clearer guidance, and responsive communication are essential for improving user experience in digital tax reforms.